PENINGKATAN KOMPETENSI FISIKA SISWA MENGGUNAKAN PENDEKATAN OPEN ENDED DENGAN METODE PENEMUAN TERBIMBING DI KELAS X SMA NEGERI 1 ULAKAN TAPAKIS - Dasmita, Dasmita (Menara Ilmu, 2020)
The problem of this research were low students’ competences; Lack of students’ participations, and low students’ ability in expressing their ideas, and also the students’ unwillingness to take part in practical laboratory activities. As a result, the students became passive learners. To overcome such problems, the researcher interested to conduct a research by using Open-Ended and Guided Discovery Methods on Physics subject at grade X of SMA Negeri 1 Ulakan Tapakis in order to improve the students’ ability in learning. The type of this research was a classroom action research. The research conducted on grade X of SMA Negeri 1 Ulakan Tapakis on academic year of 2011-2012. The subject of this research was class X-2 with a total sample of 30 students. Each cycle consists of planning, implementation, observation and reflection. The instrumentation used were observation sheets and field notes. The technique of analyzing data used was descriptive analysis.The results of the research were shown that the students’ cognitive competence was improved from 46.67% on first cycle to 83.33% on second cycle. Students’ psychomotor competence increased from 49.09% on first cycle to 84.45% on second cycle. The same condition also happened to students’ affective competence, on first cycle only 26.46% students’ got A but at the end of second cycle increased to 73,69%. In brief, the research proved that Open-Ended and Guided Discovery methods were significantly improved the students’ competences in learning Physic. Keywords:competence physics Students, SMA Negeri 1 Ulakan Tapakis